Opportunities and Challenges of Socio-Cultural Cooperation in China’s Belt and Road Initiative in Indonesia - Yuniarto, Rudolf (Universitas Muhammadiyah Yogyakarta, 2020)
In addition to developing international relations, trade and infrastructure financing, China’s Belt and Road Initiative (BRI) also includes efforts to build human relations and socio-cultural exchanges between China and other countries. Human relations and socio-cultural exchanges have not been widely discussed in previous China’s BRI studies, such as labor migration, tourism relations, education, and social and cultural exchanges. All sectors have the potential to further increase in the amount and larger scale of cooperation in the future. This paper examined the extent to which this cooperation has developed in Indonesia. Furthermore, what are the constraints, to what extent are the critical roles of human relations and socio-cultural exchanges, and what matters should be followed up to strengthen relations between Indonesia and China?